DELIBERATE SELF HARM! AN INQUIRY OF A POTENTIAL LINK WITH DEPRESSION - Khan, Farrukh hayat; ., Abid Aftab; ., Tarique Arain (Pakistan Armed Forces Medical Journal, 2011)
Objective: To determine the frequency of depression in patients of first episode of Deliberate Self Harm in patients visiting Emergency Dept of a tertiary care hospital. Place and Duration of Study: PNS Shifa hospital, Karachi. One year 1st Jan 2007 to 31st Dec 2007 Patients and Method: In this study all the patients (n=60) reporting to Emergency Dept with history of self harm were assessed. All the first episode cases between age groups 14-40 yrs (n=60) were included after formal consent. Statistical ratios and percentages were calculated and various variables between the male vs. female, depression and suicidal intentions and other data were computed and plotted using SPSS program and presented on charts and tables. Results: Male to female ratio was 2:1, Married to single ratio was 2:3, 37 (62%) had mild-moderate one (2%) was severely depressed and rest of the sample (n=22) had no or minimal scores on HAM-D 17. Intent of suicide on Beck suicide scale was low or nil 80% patients; and 20% patients had a moderate or high intent of suicide. Conclusion: The study shows a high percentage of depression in deliberate self harm group. Patients of deliberate self harm often go unidentified; Prompt management and assessment of the high risk group especially those with depression is required to prevent and to decrease overall mortality and morbidity associated with deliberate self harm.